2018
DOI: 10.1371/journal.pone.0206585
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hot air treatment and chitosan coating on citric acid metabolism in ponkan fruit during cold storage

Abstract: In citrus fruit, citric acid is the predominant organic acid which influence fruit taste, flavor and quality. The effect of hot air treatment (HAT 40°C, 48 h) and 1.0% chitosan coating on the change of organic acids and the related gene expression of citric acid synthesis and degradation in ponkan (Citrus reticulata Blanco) fruit during cold storage have been studied. The results showed that citric acid was the main organic acid in fruit, the trend change of citric acid content was consistent with total organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Researchers reported that for fruits stored for 3 weeks at 5 • C followed by shipping and marketing simulations at 20 • C and 13 • C for 4 and 3 days, respectively, although the HTFA treatment increased the SSC/TA ratio, it also caused an important damage in product flavor. In a previously published article, Gao et al [51] studied the effects of hot air treatment (HAT 40 • C, 48 h) on the citric acid contents of ponkan fruits. Researchers noted that the citric acid concentration (consistent with TA) decreased during the storage duration while the HAT promoted citric acid degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers reported that for fruits stored for 3 weeks at 5 • C followed by shipping and marketing simulations at 20 • C and 13 • C for 4 and 3 days, respectively, although the HTFA treatment increased the SSC/TA ratio, it also caused an important damage in product flavor. In a previously published article, Gao et al [51] studied the effects of hot air treatment (HAT 40 • C, 48 h) on the citric acid contents of ponkan fruits. Researchers noted that the citric acid concentration (consistent with TA) decreased during the storage duration while the HAT promoted citric acid degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2019) demonstrated that UV-treated peaches stored at 1°C were characterized by a down-regulation of aconitase and NADP-malic enzyme activities and gene expression levels, but higher levels of citrate synthase and NAD-malate dehydrogenase, resulting in a reduced degradation of citric and malic acids. Interestingly, pre-cold storage hot air treatment (40°C, 48 h) in ponkan orange promoted citric acid degradation, attributed to regulation by ATP citrate lyase (ACL) and g-aminobutyric acid (GABA) pathways (Gao et al, 2018).…”
Section: Organic Acid Metabolismmentioning
confidence: 99%
“…Heat treatments have been recently studied in citrus fruits. Gao, Kan, Wan, Chen, Chen & Chen (2018) applied hot air treatments (40 C, 48 h) and 1% chitosan coating in mandarin fruits, with different effects on citric acid degradation. Soto-Reyes, L opez-Malo, Rojas-Laguna, G omez-Salazar & Sosa-Morales, 2018 proposed microwave-assisted hot water treatments (48 C, 6 min) on grapefruits to control Mexican fruit fly, which preserved the overall quality of the fruits.…”
Section: Introductionmentioning
confidence: 99%